Description of the Health Literacy and Physical Literacy Levels of Children Aged 12-15 Years - Alamsyah Alamsyah; Wahyu Indra Bayu; Herri Yusfi; Fitri Agung Nanda (Multilateral: Jurnal Pendidikan Jasmani dan Olahraga)
Health has become a crucial aspect of life, where health literacy and physical literacy are two interconnected concepts related to individual health in understanding wellness and learning involving one's physical activities. This research aims to determine students' level of knowledge regarding health literacy and physical literacy. The study was conducted using a descriptive quantitative approach, employing survey methods. The research was carried out at SMPN 2 Kasui in the Waykanan district of Lampung province. Data collection was conducted through questionnaires involving all students. Based on the research findings, it was revealed that most of the students have yet to fully comprehend the concepts of health literacy and physical literacy. Limited educational resources and inadequate facilities have contributed to students possessing minimal knowledge about health. The results indicated that the level of health literacy knowledge among students at SMPN 2 Kasui is problematic. The distribution of physical literacy knowledge data among all students revealed that 20% fall into the 'low' category, 77% are 'moderate,' and 3% are classified as 'good.'